Photosynthesis in lightfleck areas of homobaric and heterobaric leaves - Pieruschka, Roland; Chavarría-Krauser, Andrés; Schurr, Ulrich; Jahnke, Siegfried (The journal of experimental botany, 2010)
Leaves within a canopy are exposed to a spatially and temporally fluctuating light environment which may cause lateral gradients in leaf internal CO2 concentration and diffusion between shaded and illuminated areas. In previous studies it was hypothesized that lateral CO2 diffusion may support leaf photosynthesis, but the magnitude of this effect is still not well understood. In the present study homobaric leaves of Vicia faba or heterobaric leaves of Glycine max were illuminated with lightflecks of different sizes, mimicking sunflecks. Photosynthetic properties of the lightfleck areas were assessed with combined gas exchange measurements and chlorophyll fluorescence imaging. Lateral diffusion in homobaric leaves with an interconnected intercellular air space stimulated photosynthesis and the effect was largest in small lightfleck areas, in particular when plants were under drought stress. Such effects were not observed in the heterobaric leaves with strongly compartmented intercellular gas spaces. It is concluded that lateral diffusion may significantly contribute to photosynthesis of lightfleck areas of homobaric leaves depending on lightfleck size, lateral diffusivity, and stomatal conductance. Since homobaric leaf structures have been reported for many plant species, it is hypothesized that leaf homobary may have an impact on overall plant performance under conditions with a highly heterogeneous light environment.